Intestinal Parasitic Investigation in Temple Rhesus Monkeys of Kathmandu - Jha, Anwita; Chalise, Mukesh K; Shrestha, Rebati M; Karki, Kedar (The Initiation, 2011)
The rhesus monkeys (Macaca mulatta) of Kathmandu come into frequent contact with humans and due to their habit of residing in the religious and parkland of human proximity, there is possibility of zoonotic and anthroponotic disease transmission between them. So, a prevalence survey of gastrointestinal parasites of these monkeys was conducted during April and May 2005 in three temples Pashupatinath, Swyombhunath and Tripureshwor. Total 121 fresh faecal samples, were collected randomly from these areas that were about fifteen percent of total monkey population. The faecal samples were analyzed by direct smear and concentration methods. The overall parasitization rate was 76.86% with the highest in Pashupatinath (86%) followed by Swyombhunath (74%) and Tripureshwor (61.9%). About 27.96% had single infection while 72.04% had mixed infection. This showed that the presence of one parasite reduced the immunity of the host as a result multiple infections existed. Parasite identifications were based upon the size and appearance of trophozoites, cysts, eggs and larvae of parasites. Both protozoan and helminthes parasites were observed in varying rates in three temples. Three species of protozoa and ten species of helminths were detected by microscopical examination of faecal samples. Human is always prone to be infected by most of these parasites so they are of zoonotic importance. The study will enrich the information on temple monkeys and will support their ecological management in human proximity. DOI: http://dx.doi.org/10.3126/init.v4i0.5530 The Initiation Vol.4 2011 1-7